2013
DOI: 10.1111/hepr.12065
|View full text |Cite
|
Sign up to set email alerts
|

Role of 6‐month abstinence rule in living donor liver transplantation for patients with alcoholic liver disease

Abstract: Living donor LT for patients with ALD who complied with the 6-month abstinence rule provides sufficient survival benefit with good compliance, compensating for the potential risks to the donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Relapse is regarded as a kind of betrayal of the donor's sacrifice. The results are similar to those obtained for non-ALD patients and that of deceased donor LT and the relapse was 8% (5.7% with the rule and 19.1% without) [37][38][39]. From this conservative standpoint, the alcoholic hepatitis is still not indicated for LDLT [37][38][39].…”
supporting
confidence: 83%
See 1 more Smart Citation
“…Relapse is regarded as a kind of betrayal of the donor's sacrifice. The results are similar to those obtained for non-ALD patients and that of deceased donor LT and the relapse was 8% (5.7% with the rule and 19.1% without) [37][38][39]. From this conservative standpoint, the alcoholic hepatitis is still not indicated for LDLT [37][38][39].…”
supporting
confidence: 83%
“…In Asia, ALD had not been regarded as an optimal indication for living donor liver transplantation (LDLT), because of the perception of a self-inflicted nature of ALD and the risk of relapse. Otherwise, there is a special relationship between the recipient and living donor considered unique, permitting LDLT in selected patients [37][38][39].…”
mentioning
confidence: 99%
“…A patient with ALC may return to a pattern of alcohol consumption, which potentially can damage the transplanted liver and affect compliance with the immunosuppressive regimen and follow‐up appointments; this may put the graft at risk . Hence, selection criteria for predicting alcohol relapse from preoperative data and postoperative education and support to keep patients away from recidivism have been strengthened …”
mentioning
confidence: 99%
“…In 1990, Bird et al reported the usefulness of an abstinence period of at least 6 months. Since then, the 6‐month rule has been the most widely used criterion . However, the length of abstinence before transplantation has not predicted alcohol relapse in some studies .…”
mentioning
confidence: 99%
“…This study followed a 6-month abstinence rule and participation in a rehabilitation program, psychiatric consultation, and written agreement declaring an intention of lifetime abstinence. 36 We found relapse rate of 10.7% in 270 LDLT patients (published in abstract form). 37 The lower relapse rate in our series could be secondary to LDLT, active psychiatrist involvement, close follow-up of patients after liver transplantation, and role of strong Indian family support.…”
Section: Living Donor Liver Transplantation and Alcoholic Liver Diseasementioning
confidence: 77%